Differential pulse polarography and voltammetry with an automated microprocessor-based polarograph and a static mercury drop electrode - Tan, W. T.; Tan, G. S. (Universiti Pertanian Malaysia, 1985)
Differential pulse polarography using an automated, microprocessor- based polarographic analyzer equipped with a static mercury drop electrode has been evaluated with respect to pulse amplitude, scan rate, drop time (t), and drop area. Variation of peak current, z"p' with drop area and t - Y2, with some pulse amplitudes agree reasonably well with theory. However, dependence of and E or i scan rate and on pulse amplitude at very large and very small amplitudes was found to devide fron i theory. Similar trends were also found for anodic stripping voltammetry when differential pulse stripping was used. The precision attainable by both techniques was good. Copper peaks demonstrated good precision only when copper was plated out individually during anodic stripping voltammetry.